CFY-Stack Technology: The Next Design. (2nd June 2015) - Bienert, Christian; Brandner, Marco; Skrabs, Stefan; Venskutonis, Andreas; Sigl, Lorenz S.; Megel, Stefan; Becker, Wieland; Trofimenko, Nikolai; Kusnezoff, Mihails; Michaelis, Alexander
Abstract : The stack concept of electrolyte supported cells is applicable for both, SOFC as well as SOEC. High power densities and efficiencies comparable to stacks based on anode supported cells can be achieved, however, in unison with higher robustness. Incorporating an electrolyte made of fully scandia-stabilized zirconia paired with chromium-base CFY interconnects of matched CTEs, a feasible stack concept was created with the focus on long-term stability in regard to high temperature corrosion and thermal cycling. Onward development of the stack design as well as stack data of more than 20, 000 hours of a single stack are presented. Using the same material combinations and the same footprint as for the MK351-design, the newly developed MK352-design allows for easier stack assembling and system integration. Slight modifications in interconnect design enable lower pressure drops over the stack, which, paired with enhanced tolerance chains lead to enhanced stack performance, especially in regard to system cycling.